Ectopic sebaceous gland hyperplasia in neonates oral mucosa: 3 case studies (Archives of Pediatrics of Uruguay, 2022)
Sebaceous gland hyperplasia is a common transient and benign finding in neonates. After androgenic hormonal stimulation, there is a gland overgrowth mainly in the nose and cheeks where there is a greater density of glands.Ectopic sebaceous gland hyperplasia, called Fordyce’s Granules (FG), is exceptional in neonates and it is reported in approximately 1% of newborns and frequently located in the oral mucosa.FGs are described as 1-3mm2 yellowish-white papular and vesicular lesions. Neonatologists or pediatricians may confuse these clinical features with infectious diseases, leading to invasive tests and unnecessary treatment.We describe three clinical cases of neonates with diagnosis of ectopic sebaceous gland hyperplasia located in the oral mucosa, with the aim of reviewing the etiology, clinical characteristics, differential diagnoses and evolution of this benign entity.Conclusions: ectopic sebaceous gland hyperplasia of the lips is a self-limited benign finding occurring infrequently in newborns. The clinical recognition of this entity is important to avoid inaccurate diagnoses or unnecessary treatment.
Keywords: Hyperplasia; Fox-Fordyce disease; Newborn